Applicationof Oodev and Turmeric Flour in Maturing of Mahseer Fish (Tor douronensis) Broodstock - Faridz, Achmad; Alawi, Hamdan; Sukendi, Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThis research was conducted on 26 September – 26 October 2018 in the Regional Technical Implementation Unit TheLukup BadakFish Hatcheryin Central Aceh District. The purpose of this study was to determine the effect of Oodev and turmeric flour doses on maturation of Mahseer fish (Tor douronensis). The method used was a Completely Randomized Design (CRD) with 1 factor and 5 levels of treatment where each treatment used 3 replications to obtain 15 experimental units. The treatments in this study were giving Oodev 0 ml / kg broodstock turmeric flour 0 g / kg of feed, Oodev 0.5 ml / kg of broodstock and turmeric flour 0 g / kg of feed, Oodev 0.5 ml / kg ofbroodstock and turmeric flour 0.25 g / kg of feed, Oodev 0.5 ml / g of broodstock and turmeric flour 0.5 g / kg of feed and Oodev 0.5 ml / kg ofbroodstock and turmeric flour 0.75 g / kg of feed. The results showed that Oodev and turmeric flour effect had a significant effect (P <0.05) on the maturation of Mahseer fish (Tor douronensis). Oodev 0.5 ml / kg of broodstock and turmeric flour 0.75 g / kg of feed is the highest treatment for maturation of Mahseer fish (Tor douronensis) which results in increased broodstock weight of 116.67 g, growth rate of relative parent weight of 11, 67%, Gonad Maturity Index (GMI) of 5.76%, increase in egg diameter of 1.57 mm and relative egg diameter increase of 157.29%. Key Word : Tor douronensis, Oodev, Mahseer, Turmeric flour, Gonad, Egg diameter